The Effectiveness Of Maturation Stimulation Method On Fecundity And Egg Diameter Of Freshwater Lobster (Cherax quadricarinatus) - Siti Komariyah; Teuku Fadlon Haser; Andika Putriningtias (University of Prof. Dr. Hazairin, SH, 2021)
Freshwater lobster is a fishery commodity that has many advantages so that the Ministry of Maritime Affairs and Fisheries has made Freshwater lobster a mainstay aquaculture commodity. As a result, the demand for Freshwater lobster seeds is increasing, while naturally Freshwater lobster only spawns 2 times per year. One of the efforts to improve the reproductive performance of Freshwater lobster is the selection of the appropriate maturation stimulation method. So it is necessary to investigate several methods of stimulating Freshwater lobster broodstock maturation that can improve reproductive performance, namely fecundity and egg diameter of Freshwater lobster. The design used in this study was a completely randomized design, with 4 treatments and 3 repetitions. The treatments in this study were P1 (control), P2 (eyestalk ablation), P3 (addition of vitamin E to feed), and P4 (hormone injection). Based on the results of the study, the treatment of different maturation stimulation methods gave no significant effect (P>0.05) on fecundity and egg diameter, but was significantly different from the control treatment. So it can be concluded that different maturation methods can only accelerate maturation in Freshwater lobster broodstock compared to control treatments.